Pengaruh Working Capital Management terhadap Profitabilitas Perusahaan Manufaktur Indeks Lq45 - Yanti Hasbian Setiawati (ManBiz: Journal of Management and Business, 2022)
Every organization that is profit-oriented or non-profit, regardless of the size and nature of its business, requires a number of working capital. Working capital is the most important factor for maintaining liquidity, survival, solvency and profitability of the business. Working capital management is one of the most important areas when making comparisons between a company's liquidity and profitability, which involves a decision on the number of current assets and asset financing. The efficiency of working capital management is very important especially for manufacturing companies, where most of its assets consist of current assets. This directly affects the profitability and liquidity of the company. The trade off between liquidity and profitability is important because if working capital management is not given, companies tend to fail and face bankruptcy. The importance of efficient working capital management is undoubted. Because working capital provides strength for each economic and management unit which is considered to be one of the most important functions of corporate management. Therefore, given the importance of working capital management management this research was focused on evaluating the effect of working capital on profitability, in the LQ45 index manufacturing company for the 2003-2007 period. Key Words: working capital management, profitability, manufacturing LQ45Y index